The role of cardiac biomarkers in early detection of cardiotoxicity in breast cancer treated with trastuzumab in the adjuvant setting: a systematic review - Una Cidon, Esther; Hickish, Tamas; Alonso, Pilar (Open Science Journal, 2021)
Trastuzumab, a humanized monoclonal antibody against the extracellular domain of human epidermal growth factor receptor 2 (HER-2) prolongs disease-free survival (DFS) and overall survival (OS) in patients with early-stage breast cancer. Although it is generally well tolerated, it has been associated with cardiotoxicity, mainly a reduction of left-ventricular ejection fraction (LVEF), especially if the patient has received anthracyclines. It is generally known that a drop in LVEF has limited diagnostic ability. Therefore, the identification of serum biomarkers of cardiotoxicity, able to detect damage at an earlier phase, has become ideal. Troponins (conventional and high sensitive), natriuretic peptides, reactive C protein (CRP), myeloperoxidase (MPO), etc are different molecular markers which have been assessed to check their role in the detection of treatment induced cardiotoxicity (CTIC) with controversial results. OBJECTIVE This systematic review will synthesize available evidence assessing the role of different serum biomarkers in early prediction of cardiotoxicity in breast cancer patients treated with adjuvant trastuzumab. METHODS/DESIGN Systematic review conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Distinct scientific databases such as Google Scholar, Pubmed, EBSCOhost, and PsycINFO were searched to aid in the investigation of the research problem. Randomized clinical trials (RCT) and observational studies of patients with early breast cancer receiving adjuvant trastuzumab were eligible for inclusion. Two investigators have independently evaluated those studies and used standardized data extraction templates to collect data on the study and patients’ characteristics. RESULTS 11 articles were selected, one RCT and ten observational studies. The most studied biomarker was N-terminal-pro-brain natriuretic peptide (NT-proBNP) followed by troponins. Findings showed that NT-proBNP was not predictive of CTIC while conflictive results were seen with troponins. One study showed a predictive role of high sensitive (hs) CRP and another found a relationship with the levels of MPO. CONCLUSION Biomarkers offer a unique potential to improve the effectiveness and safety of trastuzumab through timely detection of CTIC and prompt initiation of appropriate treatment. Troponins I and T have shown a predictive role in early detection of CTIC but further research would be needed to enable more insight and improve the overall patient outcome.